Spatial Decision Support Systems for Landscape Ecological Evaluations in the Southwest Florida Feasibility Study - Leonard Pearlstine; Donald L. DeAngelis; Frank J. Mazzotti; Tomma Barnes; Michael Duever; Janet Starnes (EDIS, 2006)
The objective of the Southwest Florida Feasibility Study (SWFFS) is to develop a comprehensive and ecologically sound regional plan for water resources in southwestern Florida. This study will address the health of upland and aquatic ecosystems and will consider a variety of parameters including water flow, water quality, water supply, maintenance of existing flood protection, wildlife, biological diversity, and natural habitat. This document is CIR 1479, one of a series of the Wildlife Ecology and Conservation Department, UF/IFAS Extension. Original publication date: January, 2006.